The missing martyrs: why are there so few Muslim terrorists? - Kurzman, Charles (Oxford University Press, 2019)
Why there are so few muslim terrorists -- Radical sheik -- Thoroughly modern mujahidin -- Liberal Islam versus revolutionary Islamism -- Uncle Sam versus Uncle Usama -- Predicting the next attacks.